Quirky History 2 : Strange Stories From History - Mini Menon (Bharat Harper Collins Publishers Ltd, 2023)
"The Quirky History series is back with another collection of bizarre believe it or not tales ... A tantric temple on a frog, a lady turning into a sweet, the world's biggest gold haul from a field, a Maratha fort in London, Hitler's gift to the Maharaja of Patiala, a celebrity rhinoceros called Clara, and a plan to sell the Taj! Can it get quirkier than that?! See history come alive and pop right out of this book through this amazing collection of unusual stories! ""Get ready to be amused, amazed and delighted by this new collection of quirky stories and see history come alive yet again."" - Ruskin Bond"
Keywords: Curiosities & Wonders / Facts -- Curiosities & Wonders / Facts